2022
DOI: 10.1002/jdn.10212
|View full text |Cite
|
Sign up to set email alerts
|

Chronic caffeine consumption improves the acute sleep deprivation‐induced spatial memory impairment while altering N‐methyl‐D‐aspartate receptor subunit expression in male rats

Abstract: Caffeine is a psychostimulant substance that is mostly used to prevent fatigue, increase alertness, and ameliorate sleep loss situations. In this study, we aimed to investigate the effect of chronic caffeine consumption on learning and memory functions and related genes in rapid eye movement (REM) sleep‐deprived rats. During the neonatal period (postnatal day [PND] 28) Wistar albino male rats (n = 32) were randomly assigned into four groups: Control (C), caffeine application (Cf), acute REM sleep‐deprivation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In our study, there was a decrease in the Cf group, but it was not significant. In our previous study, Cf did not affect BDNF and NR2A levels in the hippocampus, and a decrease was found in NR2B, but it was not significant (Keloglan‐Musuroglu et al, 2022). In a study was found that BDNF increased with age and Cf solution (0.1 mg/mL) during 30 consecutive days prevented this increase (Sallaberry et al, 2013).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study, there was a decrease in the Cf group, but it was not significant. In our previous study, Cf did not affect BDNF and NR2A levels in the hippocampus, and a decrease was found in NR2B, but it was not significant (Keloglan‐Musuroglu et al, 2022). In a study was found that BDNF increased with age and Cf solution (0.1 mg/mL) during 30 consecutive days prevented this increase (Sallaberry et al, 2013).…”
Section: Discussionmentioning
confidence: 81%
“…Cf (Sigma Aldrich, Saint Louis, MO) was added to the drinking water of the Cf and SICf groups at a daily of 0.3 g/L for 4 weeks (Alkadhi & Alhaider, 2016; Keloglan‐Musuroglu et al, 2022). The estimated amount of Cf that each rat consumed per day was 1–2 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Sleep deprivation also alters the expression of NMDA receptors in the hippocampus. Brief sleep restriction increases the NR2A subunit of NMDA receptors, changing the NR2A/NR2B ratio and impacting hippocampal LTP 80 . While alterations can be reversed with sleep recovery, the long‐term effects of prolonged sleep restriction remain unclear.…”
Section: The Potential Mechanisms Driving Sd‐induced Pndmentioning
confidence: 99%
“…Brief sleep restriction increases the NR2A subunit of NMDA receptors, changing the NR2A/NR2B ratio and impacting hippocampal LTP. 80 While alterations can be reversed with sleep recovery, the long‐term effects of prolonged sleep restriction remain unclear. Additionally, sleep deprivation significantly reduces the expression and phosphorylation levels of glutamate receptors in the posterior hippocampus, weakening glutamate signaling and affecting LTP.…”
Section: The Potential Mechanisms Driving Sd‐induced Pndmentioning
confidence: 99%
“…Caffeine is an anhydrous form (Sigma Aldrich, Saint Louis, MO, USA, lot: r068K8730V) was administered via drinking water (0.3 g⁄L) chronically for 4 weeks and prepared daily [19,20]. The daily consumption of caffeine by each rat was ensured to be nearly 16-20 mg.…”
Section: Caffeine Treatmentmentioning
confidence: 99%